Midbrain Infarction Presenting With Monocular Elevation Palsy and Ptosis. Issue 2 (June 2015) - Choi, Yun-Ju; Lee, Seung-Han; Park, Man-Seok; Kim, Byeong C.; Kim, Myeong-Kyu
<x xml:space="preserve">Abstract</x> Abstract: A combination of monocular elevation palsy and ptosis is usually characteristic of an extra-axial lesion of the superior branch of the third nerve. We report an unusual case of monocular elevation palsy and ipsilateral ptosis due to midbrain infarction involving the third nerve fascicle. In addition, we conducted a review of the literature of similar cases and produced an overlay image of the magnetic resonance scans from these reports. The overlapping regions primarily were located in the midbrain between the red nucleus and cerebral peduncle. This correlated with involvement of the lateral portion of the third nerve fascicle containing fibers to the superior rectus and levator palpebrae.